2019
DOI: 10.1155/2019/2941501
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Euthyroid Baby following Hyperthyroidism in Twin Gestation with Coexisting Complete Hydatidiform Mole

Abstract: Context. Gestational trophoblastic disease (GTD) is a rare complication of pregnancy, ranging from molar pregnancy to choriocarcinoma. Twin pregnancies with GTD and coexisting normal fetus are extremely rare with an estimated incidence of 1 case per 22,000–100,000 pregnancies. Molecular mimicry between human chorionic gonadotrophin (hCG) and thyroid-stimulating hormone (TSH) leads to gestational trophoblastic hyperthyroidism (GTH) which is further associated with increased maternal and fetal complications. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…hCG and TSH share a molecular resemblance that leads to gestational trophoblastic hyperthyroidism, which is also linked to an increase in maternal and fetal problems. 28 In our case, she had gestational trophoblastic hyperthyroidism, for which she was treated with thioamide and beta-blocker, underwent inpatient follow-up and care, and improved and gave birth to alive euthyroid newborn. Some authors reported an increased risk of severe preeclampsia (25.8%) in complete hydatidiform mole with a coexisting live fetus, while others found no significant differences with singleton complete molar.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…hCG and TSH share a molecular resemblance that leads to gestational trophoblastic hyperthyroidism, which is also linked to an increase in maternal and fetal problems. 28 In our case, she had gestational trophoblastic hyperthyroidism, for which she was treated with thioamide and beta-blocker, underwent inpatient follow-up and care, and improved and gave birth to alive euthyroid newborn. Some authors reported an increased risk of severe preeclampsia (25.8%) in complete hydatidiform mole with a coexisting live fetus, while others found no significant differences with singleton complete molar.…”
Section: Discussionmentioning
confidence: 68%
“…hCG and TSH share a molecular resemblance that leads to gestational trophoblastic hyperthyroidism, which is also linked to an increase in maternal and fetal problems. 28 In our case, she had gestational trophoblastic hyperthyroidism, for which she was treated with thioamide and beta-blocker, underwent inpatient follow-up and care, and improved and gave birth to alive euthyroid newborn.…”
Section: Discussionmentioning
confidence: 68%
“…Molar pregnancies were not included in this review due to their different pathophysiology. Such patients face a considerable risk of developing severe hyperthyroidism constituting one of the main challenges for caregivers ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complete hydatidiform mole with a coexisting live fetus (CHMCF) is a rare condition. The estimated incidence is 1 per 22 000–100 000 pregnancies 1 2. In absolute terms, a study by Rohilla3 in 2015 found 177 documented cases with consequent 66 live births to date.…”
Section: Discussionmentioning
confidence: 99%